Peter Zajac and his Attempt at Pulsatory Aesthetics - Michal Harpáň (Slovenska Literatura, 2016)
Peter Zajac advocates the synergy approach to literature in his monographs and studies. In his opinion, literature deals with the theme of problem situations, which do not necessarily have to be crises, but also acts of anticipating and defusing a crisis.The functional sign of their presentation is the pulsatory character as an output of multidimensional nature and manifold interaction, which resulted from thematizing the life world. The creativity of literature seen in this way is closely related to the dynamics of creation, construction, reading, impact of a literary work.